2017
DOI: 10.12688/f1000research.11697.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding basophil functions in vivo

Abstract: Basophils are mainly known as pro-inflammatory effector cells associated with allergy and helminth infections. Although they were identified over 130 years ago, their in vivo functions are still poorly understood. New insights into basophil development and function have been gained by the development of various transgenic mouse lines and staining techniques to detect and purify these cells from different organs. Several studies over the past few years have identified unexpected functions for basophils, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…In general, the role of basophils during primary infection with helminths appears to be limited (6). Despite previous studies using depleting Abs that suggested a role of basophils during Th2 T cell priming, Th2 T cell expansion was not affected in (22).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In general, the role of basophils during primary infection with helminths appears to be limited (6). Despite previous studies using depleting Abs that suggested a role of basophils during Th2 T cell priming, Th2 T cell expansion was not affected in (22).…”
Section: Discussionmentioning
confidence: 94%
“…The role of basophils during helminth infection has been studied using basophil-deficient mice or basophil-depleting Abs (5). Thus, most studies focused on the role of basophils in gastrointestinal nematode infection (6). In this context, we have shown that basophils are dispensable for the control of the tissue-migrating Strongyloides ratti L3 during primary infection and contribute to the control of parasitic adults in the intestine at the peak of infection (7).…”
Section: Introductionmentioning
confidence: 98%
“…A higher interleukin-6/10 ratio has been associated with increased risk of recurrence of BCG-treated patients, while another study found that IL-2 urine levels showed an earlier peak than IL-10 levels in responders vs. non responders. Basophils may have a role in BCG-treated bladder cancer patients because of their ability to facilitate Th2 polarization by secreting IL-4 and skewing antigen-presenting cells towards a type 2 response [17]. In fact, studies in mouse models have shown that depletion of basophils can impair Th2 polarization [18] and that Th2 responses to cysteine protease are mediated by a complex interplay between migratory dermal dendritic cells (DCs) and basophils positive for interleukin 4 (IL-4) via ROS-mediated signaling [19].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their phenotypic similarity with mast cells and their rarity, basophils had often erroneously been considered as blood-circulating precursors of tissue-resident mast cells or minor and possibly redundant relatives of mast cells, and therefore neglected in immunological studies ( 29 ). Recent development of tools useful for functional analysis, including genetically-engineered mice deficient only in basophils ( 30 36 ) ( Figure 1 ), has successfully illustrated the nonredundant roles of basophils, distinct from those played by mast cells, in a series of immune responses, including protective immunity to parasitic infections, allergic inflammation, autoimmune diseases, and regulation of innate and acquired immunity ( 37 39 ). In this article, we focus on the cellular and molecular mechanisms underlying ATR that have been clarified in animal models of tick infestation.…”
Section: Introductionmentioning
confidence: 99%